2023
DOI: 10.14569/ijacsa.2023.0140606
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Digital Model to Promote Virtual Teaching and Learning for Autism Care Centres

Abstract: The COVID-19 pandemic has led to temporary school closures affecting over 90% of students worldwide. This has exacerbated educational inequality, particularly for students with learning disabilities such as autism spectrum disorder (ASD), whose routines, services, and support they rely on have been disrupted. To address this issue, it is important to investigate virtual teaching and learning (VTL) strategies that can provide a more effective learning experience for these unique learners. The main objectives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…ICT provides interactive and customizable learning experiences, offering clear boundaries, control, and attention-grabbing features. Technology enables students with special needs to access tasks that would otherwise be difficult for them [13], [14], [15], [16].…”
Section: Virtual Teaching and Learningmentioning
confidence: 99%
“…ICT provides interactive and customizable learning experiences, offering clear boundaries, control, and attention-grabbing features. Technology enables students with special needs to access tasks that would otherwise be difficult for them [13], [14], [15], [16].…”
Section: Virtual Teaching and Learningmentioning
confidence: 99%
“…Careful planning and implementation can make AR a powerful educational tool.With the potential to provide students with immersive and interactive learning experiences that surpass the constraints of conventional teaching methods, augmented reality (AR) has the potential to revolutionise the primary school education system. The author in [21], [22] are just two of the many studies that have shown how AR improves student learning outcomes. discovered that AR-based virtual reality walkthroughs can effectively reduce motion sickness and improve learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thematic analysis, guided by framework [1], [2], identified five main themes: support, coping strategies, teaching strategies, flexibility, and communication. Within these themes, 14 subthemes were identified, covering aspects such as parental involvement [3]- [6], assistive technologies [7]- [12], individualized instruction [13]- [19], and virtual social interactions [20]- [26]. Practical implications for educators, policymakers, and researchers in special education are highlighted, offering evidence-based strategies for optimizing VTL experiences for autistic students.…”
Section: Introductionmentioning
confidence: 99%